Taxonomic and Functional Diversity of Aquatic Macroinvertebrate Assemblages and Water Quality in Rivers of the Dry Tropics of Costa Rica - Kohlmann, Bert; Vásquez, Danny; Arroyo, Alejandra; Springer, Monika (Frontiers in Environmental Science, 2021)
One of Costa Rica's driest areas is the province of Guanacaste, in the Pacific Northwest, with almost no rain during the dry season from November to April. Due to this marked seasonality, the area is covered by dry tropical deciduous forest, considered the most threatened and least known tropical ecosystem in this area. This study analyzes and characterizes the assemblages of aquatic macroinvertebrates in water bodies within the Tempisque Basin. Biological water quality was measured using the BMWP´-CR index. Macroinvertebrate assemblages were analyzed using abundance, richness, and functional feeding group approaches (FFG). Partial least square (PLS) analyses were performed, and the relationships between environmental factors and macroinvertebrate assemblages are also discussed. Macroinvertebrate assemblages were dominated numerically by mayflies, caddisflies, flies, and beetles. The BWMP´-CR index showed varying biological water quality, ranging from "very bad" to "excellent," depending on rainfall and site management. Results suggest that tropical Mesoamerican rivers contradict the “river continuum concept” because predators and scrapers displace shedders in numbers. On the other hand, the study area shows a notable high richness of the Coleoptera genera. The class Rhynchocoela (Nemertea) is reported for the first time in Central America. The results indicate that the dry forest river ecosystem shows staggering biodiversity despite the surrounding agricultural land use, probably because of their older origin concerning tropical rain forests in Central America.